2008
DOI: 10.1016/j.neunet.2008.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The state of MIIND

Abstract: MIIND (Multiple Interacting Instantiations of Neural Dynamics) is a highly modular multi-level C++ framework, that aims to shorten the development time for models in Cognitive Neuroscience (CNS). It offers reusable code modules (libraries of classes and functions) aimed at solving problems that occur repeatedly in modelling, but tries not to impose a specific modelling philosophy or methodology. At the lowest level, it offers support for the implementation of sparse networks. For example, the library SparseImp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…In [3] a generic method was presented for solving this equation efficiently, both for small synaptic efficacies (diffusion limit; the PDE becomes a Fokker-Planck equation) and for large ones (finite jumps). We demonstrated that for leaky-integrate-and-fire (LIF) neurons this method reproduces analytic results [1] and uses of the order of 0.2 s to model 1s simulation time of infinitely large population of spiking LIF neurons.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…In [3] a generic method was presented for solving this equation efficiently, both for small synaptic efficacies (diffusion limit; the PDE becomes a Fokker-Planck equation) and for large ones (finite jumps). We demonstrated that for leaky-integrate-and-fire (LIF) neurons this method reproduces analytic results [1] and uses of the order of 0.2 s to model 1s simulation time of infinitely large population of spiking LIF neurons.…”
mentioning
confidence: 91%
“…MIIND [1] is the first publicly available implementation of population density algorithms. Like neural mass models, they model at the population level, rather than that of individual neurons, but unlike neural mass models, they consider the full neuronal state space.…”
mentioning
confidence: 99%
“…This was made possible by progress in computer hardware as well as in simulation technology for models ranging from the molecular dynamics of ion channels via detailed compartmental models of individual nerve cells (neurons) to brain-scale networks of simple neuron models and field models. Today, simulation codes exist for all of these levels, but the degree of usage by the community varies (Carnevale and Hines, 2006; de Kamps et al, 2008; Helias et al, 2012; Hepburn et al, 2012; Ritter et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Various specialized tools have developed since then (O'Reilly, 2014), such as PDP ++ (McClelland and Rumelhart, 1989; O'Reilly et al, 2000), the Neural Simulation Language (Weitzenfeld et al, 2002), emergent (O'Reilly et al, 2012), the simulation platform DANA (Rougier and Fix, 2012), TheVirtualBrain (Sanz Leon et al, 2013), Topographica (Bednar, 2009) and the Neural Field Simulator (Nichols and Hutt, 2015). Similarly, efficient simulators for population-density approaches ( MIIND : de Kamps et al, 2008, DiPDE : Cain et al, 2016) as well as spiking neural networks (see Brette et al, 2007 for a review) have evolved. The foci of the latter range from detailed neuron morphology ( NEURON : Carnevale and Hines, 2006, GENESIS : Bower and Beeman, 2007) to an abstraction of neurons without spatial extent ( NEST: Bos et al, 2015, BRIAN : Goodman and Brette, 2013).…”
Section: Introductionmentioning
confidence: 99%